Analysis of N- and O-Glycosylation of Lysosomal Glycoproteins - Tokhtaeva, Elmira (Methods Mol Biol, 2017)
The vast majority of lysosomal proteins are heavily glycosylated. The present protocol describes the method of analyzing N- and O-linked glycans in lysosomal proteins of interest. The method is based on using deglycosylating enzymes, endoglycosidases, and exoglycosidases. Endoglycosidases catalyze the cleavage of an internal bond in an oligosaccharide, while exoglycosidases remove terminal carbohydrates from glycans. Different types of carbohydrate residues or chains can be removed by specific glycosidases. Removing oligosaccharides with glycosidases increases the electrophoretic mobility of a protein. This increase in mobility depends on the size and number of removed carbohydrate chains. Therefore, the treatment of lysosomal proteins with specific glycosidases followed by a western blot analysis of a protein of interest provides a way to determine which types of glycans are present in the protein by comparing the gel mobility before and after treatment.